Ruthenium Complexes Containing Heterocyclic Thioamidates Trigger Caspase-Mediated Apoptosis Through MAPK Signaling in Human Hepatocellular Carcinoma Cells - Neves, Sara P.; de Carvalho, Nanashara C.; da Silva, Monize M.; Rodrigues, Ana Carolina B. C.; Bomfim, Larissa M.; Dias, Rosane B.; Sales, Caroline B. S.; Rocha, Clarissa A. Gurgel; Soares, Milena B. P.; Batista, Alzir A.; Bezerra, Daniel P. (Frontiers in Oncology, 2019)
Herein, ruthenium complexes containing heterocyclic thioamidates [Ru(mmi)(bipy)(dppb)]PF6 (1), [Ru(tzdt)(bipy)(dppb)]PF6 (2), [Ru(dmp)(bipy)(dppb)]PF6 (3) and [Ru(mpca)(bipy)(dppb)]PF6 (4) were investigated for their cellular and molecular effects in cancer cell lines. Complexes 1 and 2 were the most potent of the four compounds against a panel of different cancer cell lines in monolayer cultures and showed potent cytotoxicity in a 3D model of multicellular spheroids that formed from human hepatocellular carcinoma HepG2 cells. In addition, both complexes were able to bind to DNA in a calf thymus DNA model. Compared to the controls, a reduction in cell proliferation, phosphatidylserine externalization, internucleosomal DNA fragmentation and the loss of the mitochondrial transmembrane potential were observed in HepG2 cells that were treated with these complexes. Additionally, coincubation with a pan-caspase inhibitor (Z-VAD(OMe)-FMK) reduced the levels of apoptosis that were induced by these compounds compared to those in the negative controls, indicating that cell death through apoptosis occurred via a caspase-dependent pathway. Moreover, these complexes also induced the phosphorylation of ERK1/2, and coincubation with an MEK inhibitor (U0126), which is known to inhibit the activation of ERK1/2, but not JNK/SAPK and p38 MAPK inhibitors, reduced the complex-induced apoptosis compared to that in the negative controls, indicating that the induction of apoptotic cell death occurred through ERK1/2 signaling in HepG2 cells. On the other hand, no increase in oxidative stress was observed in HepG2 cells treated with the complexes, and the complex-induced apoptosis was not reduced with coincubation with the antioxidant N-acetylcysteine or a p53 inhibitor compared to that in the negative controls, indicating that apoptosis occurred via oxidative stress- and p53-independent pathways. Finally, these complexes also reduced the growth of HepG2 cells that were engrafted in C.B-17 SCID mice compared to that in the negative controls. These results indicated that these complexes are novel anticancer drug candidates for liver cancer treatment.